Energetic needs and food consumption of adolescents from municipalities of Bahia (Research, Society and Development, 2021)
In order to contribute with a methodological approach, this study compared the energy needs by predictive equations, with food consumption data from a population of school adolescents, from Bahia municipalities, and also to know the food space and the meals included by this population. This is a cross-sectional study, nested in a randomized controlled trial carried out with high school students from public schools in ten cities in Bahia. Food consumption was established through a quantitative food frequency questionnaire and three food records. They were used as Dietary Reference Intakes and Schofield to calculate nutritional needs. Anthropometric (weight, height, waist circumference), sociodemographic and physical activity data were carried over descriptively and associations were tested using the chi-square test and Fisher's exact test, with a significance level of 0.95. The sample consisted of 85 adolescents, eutrophic (83.1%), active (69.5%), and most main meals (breakfast, lunch and dinner) were taken at home (> 80%). The differences between the recommended nutritional needs and food consumption were statistically relevant (p < 0.05) and indicate the need for accuracy in the investigation of outcomes related to food and energy expenditure in adolescents. The assessment of nutritional needs for population groups is important in the context of Public Health, as well as knowing the prevailing food and nutritional situation in all age groups, especially in critical life stages for the formation of new habits, such as adolescence.